Pengaruh Cross-Cultural Mentoring dan Cultural Intelligence Terhadap Cross-Cultural Adjustment Mahasiswa IISMA Universitas Padjadjaran - Zahira Salsabila; Dina Sartika (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Globalization has led to an increasing number of international students. One of the major challenges faced by exchange students is adjusting to a new culture. This study aims to examine the influence of cross-cultural mentoring and cultural intelligence on the cross-cultural adjustment of Padjadjaran University students participating in the IISMA/IISMAVO programs in 2023.This quantitative study, using a descriptive-verificative approach, involved 91 respondents. The results showed that cultural intelligence had a significant positive impact on cross-cultural adjustment. Students with high cultural intelligence were more likely to adapt to new cultural environments. Meanwhile, cross-cultural mentoring alone did not show a significant influence, but when combined with high cultural intelligence, mentoring contributed positively to improving cross-cultural adjustment.This study concludes that developing cultural intelligence is the key to enhancing students' ability to adapt to new cultures. Cross-cultural mentoring can be an effective complement, especially for students with high cultural intelligence. The findings of this study are expected to provide valuable input for the development of pre-departure programs for future exchange students.